Relationship between patients with alcoholic intoxication due to alcoholic drinks and the presence of hypoglycemia - Elier Carrera González; Jorge Luis Herrera Varela; Caridad Regla García Fernández; Lis Mahe Fernández Ros (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Alcoholic intoxication is a frequent cause of patient's medical care in recreation and enjoyment areas. Numerous are complications associated to this clinic syndrome, being described among them the hypoglycemia, intending in their treatment a customary use of glucose solutions. Objective: To determine the hypoglycemia incidence in patient with intoxication by alcoholic drinks in a recreational area "East Beach" touristic area. Material and Methods: A descriptive study was performed in patients hospitalized in an emergency service due to alcoholic intoxication and to who was carried out a capillary glycaemia analysis to reveal the presence of hypoglycemia. 59 patients with alcoholic poisoning were included in the study, without significant differences of gender, being young people and adolescents most of cases. Results: Most frequent symptoms were a level of conscience deterioration, predominating in the 62,7 % a Glasgow Coma Scale ≤ 9. 66,2 % did not ingest food before their admission. Vomiting and the dehydration was present in 62,7 and 69,4 respectively of the hospitalized patients. The transfer was necessary in 15,2 % to other hospitals to continue the studies and care. Only hypoglycemia was found in four cases for a 6,7 %, prevailing in patients older than 40 years. Conclusions: The hypoglycemia can be present in the alcoholic poisoning, being very little probable in young people and adolescents, it is related mainly to scarce food ingestion. Keywords: Poisoning, Alcoholic Drinks, Emergency Services, Hypoglycemia, Hypertonic Glucose, signs, symptoms.